Comparison of Two Serologically Distinct Ribonucleic Acid Bacteriophages I. Properties of the Viral Particles - Overby, L. R. (1966)
Overby, L. R. (University of Illinois, Urbana), G. H. Barlow, R. H. Doi, Monique Jacob, and S. Spiegelman. Comparison of two serologically distinct ribonucleic acid bacteriophages. I. Properties of the viral particle. J. Bacteriol. 91:442–448. 1966.—Two ribonucleic acid (RNA) coliphages, MS-2 and Qβ, have been characterized physically and serologically. MS-2 has an S(20, w) value of 79, a molecular weight of 3.6 × 10(6), a density of 1.422, and pH 3.9 as its isoelectric point. Qβ has an S(20, w) of 84, a molecular weight of 4.2 × 10(6), a density of 1.439, and an isoelectric point at pH 5.3. One host (Escherichia coli A-19) permits a distinction between the two on the basis of a marked difference in plaque size. They are distinct immunochemically, no serological cross-reaction being detectable.